Exploring Vincent van Gogh’s Painting’s Iconography: An Aesthetic Criticism - Subianto, Audrey Eveline; Trihastutie, Nopita (Journal of Arts and Education, 2024)
This research attempts to investigate iconography in Vincent van Gogh’s painting “The Garden of the Asylum,” as well as its connection to themes in art that are purposefully or inadvertently altered by artists in order to exhibit their work. The method used was art (aesthetic) criticism which provides a methodological umbrella for iconographic analysis.  The emphasis placed on the formal elements of art as the initial phase in the analysis is where the art criticism technique and Panofsky’s iconographic analysis connect in this study. The results demonstrate that expressionism and fauvism were later creative movements that derived from Vincent van Gogh’s unique use of color, texture, and the emotional portrayal of the human condition. A meandering path across the garden draws the viewer's attention farther into the image. The asylum’s very existence has multiple meanings and implications. It is intended to convey van Gogh's feelings of both mental and physical captivity throughout his stay. The asylum can be seen as a metaphor for the state of humanity, representing the limitations and suffering that come with being human as well as the struggle to find inner peace and spiritual transcendence in the face of hardship. In conclusion, the examination of the iconography of “The Garden of The Asylum” provides a deeper understanding of the artist’s symbolism and aims, as well as the historical context in which they are displayed, their personal and cultural significance